Antimicrobial Activity of Orange Oil on Selected Pathogens - O. F, Obidi; A. O, Adelowotan; G. A, Ayoola; O. O, Johnson; M. O, Hassan; S. C. U, Nwachukwu (The International Journal of Biotechnology, 2013)
The antimicrobial activity of orange oil extracted by steam distillation from peels of orange fruits (Citrus sinensis) was screened against some medically important microorganisms. Gram-positive bacteria (Staphyloccocus aureus 001, S. aureus ATCC 25923, Enteroccocus feacalis 002, E. feacalis ATCC 295212); Gram-negative bacteria (Pseudomonas aeruginosa 003, Escherichia. Coli 004, E. coli ATCC 29522) and fungi (Candida albicans 010, C. albicans ATCC 90028) were used. The minimum inhibitory concentration (MIC) of orange oil was estimated using disc diffusion method at concentrations ranging from (1.65-422 mg/ml). Orange oil exhibited inhibitory effects against all the organisms. The MICs observed for the isolates were: S. aureus 001 (1.65 mg/ml), S. aureus ATCC 25923 (0.69 mg/ml), Enterococcus feacalis 002 (0.09 mg/ml), E. feacalis ATCC 295212 (0.05 mg/ml), P. aeruginosa 003 (1.85 mg/ml), E. coli 004 (1.37 mg/ml), E. coli ATCC 29522 (0.82 mg/ml), C. albicans 010 (0.02 mg/ml), C. albicans ATCC 90028 (0.01 mg/ml). The GC-MS revealed that orange oil contained mainly cyclohexane, 1-methylene-4-(1-methylethenyl; bicyclo [4.1.0] hept-2-ene, 3,7,7-trimethyl; D-limonene; 1, 6-octadien-3-ol, 3,7-dimethy-l,2-aminobenzoate; 3-cyclohexen-1-ol, 4-methyl-1-(1-methylethyl); 2-cyclohexen-1-ol, 2-methyl-5-(1-methylethenyl); 2-methoxy-4-vinylphenol; 3- furanacetic acid, 4-hexyl-2, 5-dihydro-2,5-dioxo; naphthalene, 1,2,3,5,6, 8a-hexahydro-4,7-dimethyl- 1-(1-methylethyl) -, (1S-cis) and n-hexadecanoic acid. The result indicated that orange oils have antimicrobial properties and may be applied in local therapies in the treatment of diseases caused by the microorganisms tested. Further research is needed to achieve appropriate formulation.